Implementation of the Tangerang Emas (Prosperous Community Economy) Program for Micro Business Actors in Pinang Sub-District, Tangerang City - Rahmawati, Suci (Epistemik Press, 2024)
The implementation of the Tangerang Emas Program for Micro Business Actors in Pinang Subdistrict, Tangerang City is a program of the Tangerang City Government, the program was created on the basis of the Mayor of Tangerang through the Tangerang City Industry, Trade, Cooperatives and Micro, Small and Medium Enterprises Office. This study with the title